All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 32958 by artibunja last updated on 07/Apr/18
Commented by MJS last updated on 07/Apr/18
x2−3x−103x2−5x+2=13+(−3+53)x+(−10−23)3x2−5x+2==13−43×x+83x2−5x+23x2−5x+2=(x−1)(3x−2)x+83x2−5x+2=N1x−1+N23x−2==N1(3x−2)+N2(x−1)(x−1)(3x−2)==(3N1+N2)x−(2N1+N2)(x−1)(3x−2)⇒⇒3N1+N2=1∧−2N1−N2=8⇒⇒N1=9∧N2=−26∫x2−3x−103x2−5x+2dx==∫13−43(9x−1−263x−2)dx==∫13dx−12∫1x−1dx+1043∫13x−2dx==x3−12ln(x−1)+1049ln(3x−2)+C
Terms of Service
Privacy Policy
Contact: info@tinkutara.com